2015
DOI: 10.1021/acsami.5b02523
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode SERS-Fluorescence Immunoassay Using Graphene Quantum Dot Labeling on One-Dimensional Aligned Magnetoplasmonic Nanoparticles

Abstract: A novel dual-mode immunoassay based on surface-enhanced Raman scattering (SERS) and fluorescence was designed using graphene quantum dot (GQD) labels to detect a tuberculosis (TB) antigen, CFP-10, via a newly developed sensing platform of linearly aligned magnetoplasmonic (MagPlas) nanoparticles (NPs). The GQDs were excellent bilabeling materials for simultaneous Raman scattering and photoluminescence (PL). The one-dimensional (1D) alignment of MagPlas NPs simplified the immunoassay process and enabled fast, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…The Raman spectrum of the GQDs (Fig. 36,37 Similar to the G 0 mode, the evolution of this M band coupled with the increasing number of graphene layers could be inicted by that of electronic band with graphene lm structure. Furthermore, the other peak at 1750 cm À1 was clearly observed in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The Raman spectrum of the GQDs (Fig. 36,37 Similar to the G 0 mode, the evolution of this M band coupled with the increasing number of graphene layers could be inicted by that of electronic band with graphene lm structure. Furthermore, the other peak at 1750 cm À1 was clearly observed in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…[78] To detect viruses, DNA, RNA, and biomolecules, PRET-based FIs have been developed by using several plasmonic nanomaterials, including MeNPs, core/shell NPs, MeNP-CNMs, inorganic QDs, carbon dots, and GRP-QDs. [79][80][81][82][83] Takemura et al reported the detection of influenza virus through the PRET effect by using urchin-like Au NPs (u-Au NPs) and inorganic CdSeTeS QDs (Figure 3). [84] In this system, the u-Au NPs were utilized as a plasmonic substrate for energy transfer, while the QDs acted as the fluorescence indicator and captured the target influenza virus.…”
Section: Fluorescent Qds For Biosensing Systemsmentioning
confidence: 99%
“…A dual-mode surface enhanced Raman scattering and fluorescence immunoassay using graphene QDs labels on one-dimensional aligned magneto-plasmonic nanoparticles has been recently developed by Zou et al [98] and used for the diagnostic detection of tuberculosis antigen CFP-10, reaching the excellent analyte detection limit of 0.0511 pg/mL. Dong et al developed multifunctional poly(L-lactide)-polyethylene glycol-grafted photoluminescent graphene quantum dots for intracellular microRNA imaging in HeLa cells [99].…”
Section: Quantum Dots For Diagnostics and Therapymentioning
confidence: 99%